2021
DOI: 10.3390/jcm10153268
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes, Visual Quality and Visual Function of Two Presbyopia-Correcting Intraocular Lenses Made from the Same Material, but with Different Design and Optics

Abstract: This semi-prospective, parallel, comparative investigation evaluated the clinical outcomes and quality of vision (contrast sensitivity, visual function, dysphotopsia, spectacle use, overall satisfaction) after mono- or bilateral implantation of two presbyopia-correcting intraocular lenses (IOL)—the Liberty® 677MY or the AT LISA® tri 839M—in 50 eyes of 25 cataract patients. Clinical outcomes were assessed 3 and 12 months postoperatively. Eighty-nine percent of eyes implanted with the Liberty IOL and 59% of eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(56 reference statements)
3
5
0
Order By: Relevance
“…Our figures are similar to those we reported earlier following the implantation of the Bi-Flex 677TAY monofocal toric IOL [11] and are somewhat better than those reported by Bachernegg et al for the same monofocal toric lens [18]. As expected, the current residual SEQ is lower than that observed after the implantation of the Bi-Flex Liberty 677MY trifocal non-toric IOL model [19], as additional astigmatism correction improved the final refractive outcomes. The predictability of the results is found to be higher than that reported for other TTIOLs such as the FineVision Pod FT [20], and AT LISA tri 939MP [21,22].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our figures are similar to those we reported earlier following the implantation of the Bi-Flex 677TAY monofocal toric IOL [11] and are somewhat better than those reported by Bachernegg et al for the same monofocal toric lens [18]. As expected, the current residual SEQ is lower than that observed after the implantation of the Bi-Flex Liberty 677MY trifocal non-toric IOL model [19], as additional astigmatism correction improved the final refractive outcomes. The predictability of the results is found to be higher than that reported for other TTIOLs such as the FineVision Pod FT [20], and AT LISA tri 939MP [21,22].…”
Section: Discussionsupporting
confidence: 90%
“…Rotational stability was high and similar to that reported on the monofocal toric model of the same lens [11,18]. Mean IOL-rotations were comparable with those published on TTIOLs with modified L-or double C-loop haptic designs [24]; however, unlike with AT LISA tri 939MP and FineVision PodFT, no IOL-repositioning was required [19,20]. A stable IOL position contributed to the maintained refractive and visual outcomes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Optic edge profile and haptic design could also affect PCO occurrence. Nováček et al ( 20 ) compared two diffractive IOLs of the same material and discovered that the percentage of eyes undergoing Nd: YAG capsulotomy for PCO was significantly higher in the AT LISA tri group than in the Liberty (Medicontur Medical Engineering Ltd., Zsámbék, Hungary) group. They speculated that differences in haptic design might result in remarkable differences in PCO severity between groups ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nováček et al ( 20 ) compared two diffractive IOLs of the same material and discovered that the percentage of eyes undergoing Nd: YAG capsulotomy for PCO was significantly higher in the AT LISA tri group than in the Liberty (Medicontur Medical Engineering Ltd., Zsámbék, Hungary) group. They speculated that differences in haptic design might result in remarkable differences in PCO severity between groups ( 20 ). Sacu et al ( 13 ) suggested that residual LECs left in the capsular bag may invade the retro-optical capsule through the optic-edge barrier.…”
Section: Discussionmentioning
confidence: 99%